Theme-Rheme configuration in recount texts produced by Indonesian EFL students - Meiarista, Kiki; Widhiyanto, Widhiyanto (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
The topic of this study is the textual meaning in recount texts written by the fourth semester students of English Department Universitas Negeri Semarang in the academic year 2018/2019. This study is conducted since there are still limited research that is conducted in Indonesia which analyses the problems of thematic development because most of Indonesian researchers are only analyses the thematic structure and thematic development pattern. This study aimed to figure out the thematic structure, thematic development pattern, and the problems of thematic development in students’ recount texts. The text analysis of qualitative method was employed to enhance the results. The result of the thematic structures showed that the unmarked topical Theme was frequently used than the marked one in terms of topical Theme, the conjunctions became the mostly used element in textual Theme, and the modal adjuncts became the frequently used constituent in interpersonal Theme. In the case of thematic development patterns, the Theme re-iteration (constant Theme pattern) became the mostly used pattern since the function is to keep the text focused. It has been found that there were three problems of thematic development in students’ recount texts: (1) the problem of the brand-new Theme, (2) the problem of double Rheme, and (3) the problem of empty Rheme. The results of this study indicate that the students belong to beginner (inexperienced) writer.